Lessons learned from Café Scientifique public webinars on pregnancy and parenting in arthritis: perspectives from patients, clinicians, and researchers - Vienna Cheng; Preet Kang; Laurie Proulx; Neda Amiri; Mary A. De Vera (BMC Proceedings)
Abstract Background Arthritis is a group of chronic inflammatory conditions, including systemic lupus erythematosus and rheumatoid arthritis, that disproportionately impact females more than men, often during the childbearing years. Challenges with pregnancy and parenting continue to significantly impact patients and families living with arthritis, compounded by the historical lack of research that has hindered the ability to make informed family planning decisions. Objectives In ongoing efforts to broadly translate our expanding research findings in this area, we held two public webinars on pregnancy and parenting in arthritis with the following goals: 1) to create forums for discussion among researchers, patients, and clinicians; 2) raise awareness on emerging issues requiring future research; and 3) provide evidence-based, practical advice for patients, caregivers and families. Summary The first webinar on Pregnancy and Arthritis united perspectives from patients, clinicians and researchers. We learned firsthand challenges of navigating pregnancy with arthritis from patients of various backgrounds, including those who highlighted longstanding healthcare disparities. A rheumatologist specializing in pregnancy and reproductive health shared insights, concluding with the positive outlook that perinatal research is underway on emerging antirheumatic therapies. The second webinar on Parenting and Arthritis discussed evidence-based resources and strategies to support parents, integrating insights from researchers and clinicians. Conclusion These webinars illuminated the profound impacts of arthritis on patients and families and revealed knowledge gaps for future research.